2018
DOI: 10.1101/478016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hidden patterns of codon usage bias across kingdoms

Abstract: The genetic code is necessarily degenerate with 64 possible nucleotide triplets being translated into 20 amino acids. 18 out of the 20 amino acids are encoded by multiple synonymous codons. While synonymous codons are clearly equivalent in terms of the information they carry, it is now well established that they are used in a biased fashion. There is currently no consensus as to the origin of this bias. Drawing on ideas from stochastic thermodynamics we derive from first principles a mathematical model describ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…For example, the virulence of the pathogen, host defense response, environmental conditions are some of the aspects that decide the outcome of the interaction (Cheng et al 2019;Thakur et al 2019). In addition to the above-mentioned factors, codon usage bias (CUB) plays a crucial role in establishing a host-pathogen relationship (Biswas et al 2019;Deng et al 2020). CUB is defined as the phenomenon where one codon is preferred over its synonymous partners.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the virulence of the pathogen, host defense response, environmental conditions are some of the aspects that decide the outcome of the interaction (Cheng et al 2019;Thakur et al 2019). In addition to the above-mentioned factors, codon usage bias (CUB) plays a crucial role in establishing a host-pathogen relationship (Biswas et al 2019;Deng et al 2020). CUB is defined as the phenomenon where one codon is preferred over its synonymous partners.…”
Section: Introductionmentioning
confidence: 99%
“…Substituting one codon for another synonymous codon will not result in any alteration of the primary sequence of amino acids or peptides, which is primarily caused by mutations in the gene coding region, particularly mutations in the second or third nucleotides of the codon (De Mandal et al, 2020;Bailey et al, 2021). Evolutionary processes can lead to variability in synonymous codons due to a synonymous mutation or 'silent mutation' , which does not have any impact on functionality (Deng et al, 2020;De Oliveira et al, 2021). It can be concluded that codon usage bias is the consequence of mutation patterns that are unevenly distributed.…”
Section: Introductionmentioning
confidence: 99%
“…However, 18 of these amino acids and the translational start and stop signals are encoded by multiple synonymous codons 5,6 . This degeneracy of the genetic code allows coding sequences-through codon selection-to define protein production simultaneously while maintaining cellular homeostasis by regulating gene expression, translation, and protein folding 7,8 . Synonymous codon selection also influences cellular homeostasis by altering messenger (m)RNA structure, translation efficiency and speed, and accuracy 9 .…”
Section: Introductionmentioning
confidence: 99%